THE EFFECTIVENESS OF FLIPPED CLASSROOM IN THE TEACHING OF WRITING SKILL - Ali Mahrus Efendi (Language-Edu, 2020)
Writing is an activity of communicating thought within the composed shape. The use of Flipped Classroom demonstrate may make a condition that help the understudies type in with tall inspiration. Flipped Classroom Demonstrate is an imaginative instructing methodology that reverses conventional educating instead of lecturing, teachers allot video as homework to present the subject. The display study was expecting to test whether or not Flipped Classroom Strategy was effective to progress students’ score in composing descriptive content. The research used quasi experimental plan with quantitative approach. The Populace was 8th grade of MTsN 8 Banyuwangi. The samples were 8 A class consisted of 38 students as the control group  and 8 B class consisted of 38 students as the experimental. There was outside classroom and inside classroom treatment. The data sources was gathered from the pre-test and post test and being analyzed  using independent t-test in SPSS 23. The result of the post-test was 80.32 with the standard deviation is 3.786. The mean score of conventional class was 78.45 with the standard deviation is 3.600. The independent sample t-test result is 2.205(p=0.031). Since the significance value is lower than 0.05. It implies that there was significant difference score.Keywords: Flipped Classroom,Writing, Descriptive